Mindfulness-Based Islamic Spiritual Therapy on Enhancing Subjective Well-Being in Married Women with Infertility - Cholisoh, Feny; Moordiningsih (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
The inability of infertile women to have children and relevant social stigma is significantly effective in reducing subjective well-being. Therefore, this study aimed to determine the effect of mindfulness-based Islamic spiritual therapy on improving the subjective well-being of infertile married women. A non-randomized pretest posttest control group quasi-experimental design was implemented, with subjective well-being and mindfulness measured using the Subjective Well Being for Infertility Scale and Five Facet Questionnaire, respectively. A total of 10 participants were also selected and categorized into control and experimental groups. The results showed that the subjective well-being conditions of both groups were equal before therapy, regarding the Mann-Whitney U test with a value of Z = 0.000 and a 1.000 significance level (>0.05). The Mann Whitney U test was also implemented with a value of Z = -2.402 and a 0.016 significance level (<0.05), showing a difference in subjective well-being scores within the Control and Experimental Groups. Furthermore, the Wilcoxon Rank Test produced a Z-value and significance level of -2.023 and 0.043 (<0.05), respectively. This result showed an increase in subjective well-being scores within the experimental group after mindfulness-based Islamic spiritual therapy. The spiritual therapy was also used as an alternative psychotherapy to improve the subjective well-being of married women with infertility problems.